INVESTIGASI PENGARUH UKURAN PARTIKEL, KONSENTRASI, DAN SIFAT MAGNETIK ADSORBEN NANOPARTIKEL Fe3O4 TERHADAP ADSORPSI LOGAM Co dan Fe DALAM LARUTAN - , Dewi sartika ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Purification process on heave metal Co and Fe in liquid by using nanoparticle magnetit (Fe3O4) adsorbent have been investigated. The effect of particle size, concentration, remanence magnetic properties (Mr) and amplification to reduce of metal Fe and Co contents studied in this research. The result showed that the Fe3O4 adsorbent with the size of 11,5 nm was able to absorb the highest content of metal ions. Procentage of reduction of Fe and Co are 99.855% and100%, respectively. The particles which smaller particle have the higher contact surface. Moreover, concentration 0,005 g/ml and 0,006 g/ml gave the maximum reduction in the maximum degree of metals Co and Fe are 99.843% and 100%, respectively. The procentage of reduction of Co and Fe at Mr of 6,17 emu/cc are 99,936% dan 100%, respectively. The magnetic properties of absorbent would influence the reduction of metal contents. Key words: adsorption, adsorbent, and magnetite